1971
DOI: 10.1021/ja00751a024
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stabilization of cations by neighboring .sigma. bonds. General considerations

Abstract: A theory for stabilization of carbonium ions or other cations, by delocalization of neighboring bonds, is described. Such delocalization is available without changing the reactant geometry and is termed "vertical stabilization." The stabilizing influence is contrasted to the bridged-ion theory of neighboring group participation, in which the neighboring group moves toward the reaction center as the transition state is approached, and to frangomeric acceleration, in which the neighboring group moves away from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
4

Year Published

1974
1974
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(63 citation statements)
references
References 4 publications
(5 reference statements)
2
57
0
4
Order By: Relevance
“…Wie aus spektroskopischen und röntgenographischen Untersuchungen hervorgeht, wird das Dihalocarben bei la, b unter Bildung von 2a, a', b, b' ausschließlich in die ß-C-H-Funktion eingeschoben. Dieses Resultat läßt sich mit der auch bei Metallacyclen und Alkylverbindungen des Siliciums, Germaniums und Zinns diskutierten, dirigierenden Wirkung des Metalls [22,23] für die Carbenspezies erklären. Die unterschiedlichen Ausbeuten von 2a, a', b, b' bzw.…”
Section: Ergebnisse Und Diskussionunclassified
See 1 more Smart Citation
“…Wie aus spektroskopischen und röntgenographischen Untersuchungen hervorgeht, wird das Dihalocarben bei la, b unter Bildung von 2a, a', b, b' ausschließlich in die ß-C-H-Funktion eingeschoben. Dieses Resultat läßt sich mit der auch bei Metallacyclen und Alkylverbindungen des Siliciums, Germaniums und Zinns diskutierten, dirigierenden Wirkung des Metalls [22,23] für die Carbenspezies erklären. Die unterschiedlichen Ausbeuten von 2a, a', b, b' bzw.…”
Section: Ergebnisse Und Diskussionunclassified
“…unvollstän-dige Reaktion von la, auch unter verschärften Bedingungen, dürfte auf konformelle Gründe [4] zurückzuführen sein. Für eine optimale M-C-C-o-JIÜberlappung [22] ist eine M-C-C-W-trans-Anordnung [23] In den ^P^Hj-NMR-Spektren von 2a, a', b, b' wird die für Phosphamanganacycloalkane mit ungerader Ringgliederzahl auftretende Tieffeldverschiebung [1], welche auch an anderen P-haltigen Heterocyclen der Übergangsmetalle [26] Zur besseren Auflösung der in den 'H-NMRSpektren von 2a, a', b, b' auftretenden komplizierten Multiplettstrukturen wurde am Beispiel von 2 a eine Hochfeldmessung (400 MHz) durchgeführt (vgl. Abb.…”
Section: Ergebnisse Und Diskussionunclassified
“…The interaction between the methyl group orbitals and the empty ρ orbital of the cationic center is shown in Fig. Although it has been argued to the contrary on the basis of experimental data (Traylor et al, 1971), computations indicate that consider able structural modification toward nonclassical or charge delocalized structures may accompany hyperconjugation (Lathan et al, 1971;Radom et al, 1972a). The net stabilization is accompanied by charge derealization from one of the C -H bonding orbitals to the empty ρ orbital.…”
Section: B Linear Vs Bridged Structuresmentioning
confidence: 99%
“…In this context, derivatization of fullerenes using silicon and germanium atoms is an attractive method for modifying the electronic properties of fullerenes because of the electron-donating effects of silyl and germyl groups [ 16 , 17 , 18 , 19 ]. We found that the reactions of empty fullerenes with reactive silicon and germanium compounds afforded the corresponding fullerene derivatives [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%